Exploring the ecosystem services bundles and influencing drivers at different scales in southern Jiangxi, China - Liao, Qiang; Li, Tong; Wang, Qiyou; Liu, Deer (Ecological indicators, 2023)
•We analyzed the changes, trade-offs, and synergies of ESs in an ecological barrier.•We compared evolutionary mechanisms and interactions of ESs at different scales.•Multi-factors jointly affected the bundles and associated relationships of ESs. Located in the hilly and mountainous central area of the national ecological security strategic pattern (described as “two ecological barriers and three green belts”), southern Jiangxi is an important ecological barrier in southeast China and a pilot area for the national mountains-rivers-forests-farmlands-lakes-grasslands restoration projects. In recent years, the rapid economic development of the southern Jiangxi region and the rapid changes in land use, agricultural intensification, and population urbanization have severely tested this ecosystem on which people depend for their survival. Currently, studies of ecosystems and their interactions from a single spatial perspective have sprung up, but only a few studies have comprehensively analyzed different spatial scales to facilitate the sustainable development of regional ecosystems. Multi-scale studies should be carried out to quantitatively understand the relationship between ecosystem services (ESs) and socio-natural drivers, in an attempt to find a suitable scale to assess regional ESs or to achieve complementary advantages by combining multi-scales so as to conduct hierarchical management of ESs. Therefore, to better understand the interplay between ESs and to achieve the goals of sustainable development, we quantitatively analyzed the evolutionary patterns, trade-offs, and synergies of ESs. In our analysis, we also looked at bundling ESs and their drivers for seven ecosystem services at the township and watershed scales for 2000–2020 in southern Jiangxi. Crop production, meat production, water yield, carbon storage, soil retention, habitat quality, and forest recreation services were specifically quantified, and redundancy analysis was used to explore the influence degree of precipitation, temperature, elevation, slope, GDP, and population density on ESs. The results showed that most ESs have increased in southern Jiangxi, indicating spatial and temporal heterogeneity. The scale effect of trade-off and synergy showed that the spatial variation was similar, but the amplitude of variation was different. Compared with the watershed scale, the overall bundle of ESs in southern Jiangxi is better identified and clustered at the township scale. In addition, Cluster 4 at the township scale and Cluster 3 at the watershed scale can comprehensively identify high-value areas of ecosystem services in the study area. The rapid growth of GDP and population density caused by rapid urbanization were the main driving factors of the difference in ESs between the two scales in southern Jiangxi. Our results provide recommendations for governance and restoration of regional ecosystem services and support for conducting a comprehensive analysis of spatio-temporal evolutionary mechanisms and interactions of ecosystem services at different scales.